Tingkat Keterampilan Motorik Kasar Siswa di Sekolah Sepak Bola Daerah Istimewa Yogyakarta - Rafid Abiyyu Tridita; Priska Dyana Kristi; Andri Arif Kustiawan; Hadiono (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the gross motor skills level of 11-year-old students at Football Schools (SSB) in the Special Region of Yogyakarta (DIY). Gross motor skills are a fundamental basis for mastering basic football techniques, yet their mapping within non-formal coaching settings such as SSB remains rarely comprehensively studied. This study employed a descriptive quantitative method with a purposive sampling technique. The participants consisted of 47 students aged 11 years from four SSBs in DIY: SSB Matra FC (Sleman), SSB Organ (Kulon Progo), SSB Seta Muda FC (Yogyakarta City), and SSB Selabora FC (Bantul). Data collection was conducted in June 2026 using five test instruments: the 40-meter Sprint Test, Agility Run, Vertical Jump Test, Alternate Hand Wall Toss Test, and Flamingo Balance Test. Descriptive analysis proved that speed was predominantly in the Good category (44.68%), agility in the Very Good category (59.57%), leg muscle explosive power in the Very Good category (72.34%), and balance in the Very Good category (97.87%). In contrast, eye–hand coordination was predominantly in the Moderate category (74.47%). In conclusion, the gross motor skills of 11-year-old students at SSB DIY were classified as good to very good on most components, except eye–hand coordination, which requires further strengthening in training programs.